Monetary policy and stock market bubbles: the Brazilian Catch 22 - Graham, John de Freitas (2021)
This paper estimates the response of stock prices to monetary policy shocks following the framework set by Gali and Gambetti (2015) using data for Brazil. In doing so, a time-varying coefficient VAR is used for both quarterly and monthly data, separately. The evidence indicates continual periods in which stock prices respond positively to monetary policy contractions, siding with the initial finding by Gali and Gambetti (2015). However, such results is in stark opposition to commonly held “Leaning Against the Wind” approach to monetary policy and bubbles. The time-varying nature of the bubble component is further verified in subsamples representing Brasils different political-economic periods. Brazil potentially finds itself in a Catch 22: monetary policy tightening, aimed at stabilizing inflation, can lead to protracted periods of soaring stock prices.